Preclinical animal model for de novo bone formation in human maxillary sinus - Schlegel, Karl Andreas; Rupprecht, Stephan; Petrovic, Ljubinko; Honert, Christian; Srour, Safwan; von Wilmowsky, Cornelius; Felszegy, Endre; Nkenke, Emeka; Lutz, Rainer (Oral Surgery Oral Medicine Oral Pathology Oral Radiology and Endodontology, 2009)
Objectives: Up to now the effect of bone-substitute materials on de novo bone formation has been tested in a variety of preclinical animal models. We hypothesized that there is no significant difference in bone regeneration after application of autogenous bone (AB) and bone substitutes in a porcine calvarial monocortical defect model and in human maxillary sinus. Study design: Twenty-four weeks after application of ß-tricalcium phosphate (βTCP), hydroxyapatite (HA), and AB in each of 3 defects on the sculls of 6 adult pigs (N = 54) and the application in 44 sinus floor elevations (11× βTCP, 6× HA and 24× AB) in 41 patients, bone regeneration rates where compared microradiographically. Wilcoxon rank-sum test was used for statistical analysis. Results: Comparing the human with the animal specimens microradiographically, no significant difference of the mineralization rate could be found. Conclusion: The chosen porcine model is a valuable method for preclinical testing of bone-substitute materials in maxillofacial surgery. © 2009 Mosby, Inc. All rights reserved.
CRIS-Team Scopus Importer:2024-05-13